Passion fruit—a potential crop for exploration in Malaysia: a review - Md Nor, Shahidah; Ding, Phebe; Sakimin, Siti Zaharah; Ismail, Amin; Abas, Faridah (Universiti Putra Malaysia, 2022)
Passion fruit is a short-term crop with a life span of up to 2 years. Nowadays, passion fruit captures increasing demand in the global market. However, passion fruit is considered an underrated fruit in Malaysia as the production has not reached commercial cultivation. Highlighting the passion fruit as the next important commodity could rejuvenate the economy by disseminating equal benefits for both small and large-scale growers. This article provides a perspective on underlining the fruit to be explored as a commercial commodity. The fruit consists of three main components: juice, seed, and peel. Each of the fruit components has unique properties that can benefit multiple industries. In addition, strategies for successful passion fruit planting are also emphasised by farm management until the processing line produces high-quality fruit that can penetrate the global market. Therefore, a comprehensive review of passion as an essential crop could benefit Malaysia’s agriculture and processing industries.